Evaluation and selection of biochars and hydrochars derived from agricultural wastes for the use as adsorbent and energy storage materials - Lang J. (2021)
The utilization of unconventional agricultural wastes to obtain new porous carbonaceous materials, at mild pyrolysis temperatures and without complex procedures, for either water treatment and energy storage applications is important from the economic and environmental perspective. In this study, biochars and hydrochars were prepared from banana rachis, cocoa pod husks, and rice husks at 600 °C-2 h, under nitrogen flux. The prepared materials were characterized to better understand how their morphological, textural, physical-chemical and/or structural properties correlate with their methylene blue (MB) adsorption capacities. The material with the best properties (mainly SBET > 800 m2/g) and MB adsorption capacity was a novel biochar prepared from banana rachis (BW-BC). This novel material was selected for additional kinetics and equilibrium adsorption tests for lead (Pb) along with its energy storage capacity. In equilibrium test, the novel biochar reached a maximum adsorption capacity for methylene blue of 243.4 mg/g and the highest adsorption capacity for Pb(II) of 179.7 mg/g. In the kinetic adsorption test, the equilibrium adsorption value for methylene blue was 150.4 mg/g and that for Pb(II) was 159.6 mg/g. Most importantly, the performance of the BW-BC material for energy storage in supercapacitors surpassed that of the commercial activated carbon YP50F, reaching specific energy values of 6.66 and 8.52 Wh/kg in acidic and neutral electrolytes, respectively. Among the evaluated hydrochar and biochars derived of agrowastes, the biochar prepared from banana rachis showed the best properties, being potentially useful as adsorbent or as an electrode material for energy storage. © 2021 Elsevier Ltd